ISOLATION OF PARASITE CONTAMINATION IN THE SOIL - Apsari, Ida Ayu Pasti; Swacita, Ida Bagus Ngurah; Oka, Ida Bagus Made (Buletin Veteriner Udayana, 2023)
Research has been carried out on the soil around the cowshed and grazing land. Soil is the source of infection/infestation of L3 (larval stage 3), infective eggs, oocysts and mite or ticks. Soil-Transmitted Pathogens are organisms that live on the ground, but in a short time, then the continuity of the cycle requires a host. The cow acts as host in this case. The aim of the study is to isolate the type of parasitic contamination in the soil around the enclosure and grazing land. Each soil sample of 100 is collected from dry calcareous areas (Jimbaran) and the wet regions (Mengwi-Badung). The float method with MgSO4 (English salt) is modified as a method to determine the type of soil contamination. The results of the study showed 45% (90/200) soil contaminated by parasites. The parasite contamination found is coccidia oocyst, protozoa cyst, trematode and nematode worm eggs, nematode worm larvae and mite eggs and larvae. Conclusions from the results are 45% of the soil are contaminated by parasitic namely protozoa, worm eggs, mite larvae and eggs from the Bukit Jimbaran region (29%) and Mengwi (61%).